Intra-abdominal desmoplastic small round cell tumors: CT and FDG-PET/CT findings with histopathological association - CHEN, JINGJING (Oncol Lett, 2016)
Desmoplastic small round cell tumors (DSRCTs) are rare and aggressive malignant tumors. The aim of the present study was to analyze computed tomography (CT) and fluorodeoxyglucose positron emission tomography (FDG-PET)/CT imaging features of intra-abdominal desmoplastic DSRCT, and investigate the association of these features with histopathological results. The present study was a retrospective investigation of 4 patients with DSRCT. All patients underwent CT and dynamic CT, and 1 additionally underwent FDG-PET/CT scanning. Following a tumor resection, routine hematoxylin and eosin staining, and immunostaining, were performed and evaluated. Multiple large abdominopelvic masses were identified in all 4 patients; however, no indications of their site of origin were demonstrated. CT revealed soft-tissue masses with patchy foci of hypodense lesions. Contrast-enhanced CT revealed slightly or moderately heterogeneous enhancement of the lesions. Other observations from these patients included calcification (n=2), peritoneal seeding (n=3), hepatic metastasis (n=3), retroperitoneal lymphadenopathy (n=3) and ascites (n=2). FDG-PET/CT revealed multiple nodular increased FDG uptake in the abdominopelvic masses, and in the liver and peritoneum in 1 case. Intra-abdominal DSRCT demonstrated significant diagnostic characteristics on plain and contrast-enhanced CT. Multiple, bulky soft-tissue masses inside the peritoneal cavity, particularly in male adolescents and young adults, should be considered as potential cases of DSRCT. FDG-PET/CT techniques may be utilized to aid the staging of tumors.